Careers in Academic Administration - Villa-Komaroff, Lydia (Cold Spring Harb Perspect Biol, 2019)
Academic administration can be an extension of an academic career at the bench or it can run parallel to a career of discovery. To be an academic administrator at the executive level in a college or university generally requires advancement through the academic ranks to the professorial level. These positions include department chair, dean of a college, head of a center or institute, provost, senior research officer, and university or college president. Positions that can begin immediately after attaining a PhD or after a postdoctoral position include some assistant dean roles and positions in technology transfer, grants management, and laboratory management, among many others. Many of the skills developed during the pursuit of an advanced degree in the life sciences are directly applicable to these jobs. All require problem solving, critical thinking, collaboration, and the ability to communicate clearly.